COMMUNITY EMPOWERMENT THROUGH SUSTAINABLE GASTRONOMY TRAINING BASED ON STRAWBERRY PROCESSING (FRAGARIA) AS A LOCAL SUPERFOOD - Yuwantiningrum, Sri Endah; Utami, Nisa Rahmaniyah; Effendy, Marwan; Rayi A., Maritza; Zulfan V., Zidan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program aims to empower local communities by improving their capacity to process strawberries (Fragaria) as a local superfood through a sustainable gastronomy approach. The initiative promotes local economic independence, environmental preservation, and the adoption of sustainability principles in culinary practices.The program was conducted through socialization, demonstrations of the Low Temperature Cooking (LTC) technique, and hands-on training in producing processed products such as strawberry jam, low-sugar cakes, and fermented beverages. The one-day training involved 30 participants, including farmer groups, culinary MSME actors, and local residents. The evaluation revealed a 40% increase in participants’ knowledge and skills after the training. Participants also initiated the formation of small culinary business groups focusing on strawberry-based local products. The application of the zero waste concept was achieved through utilizing strawberry waste as organic fertilizer, supporting a circular economy model. This program effectively enhanced community awareness of sustainable gastronomy and fostered economic empowerment through innovation in local food processing. It demonstrates a replicable model for promoting food security, strengthening local culinary identity, and supporting sustainable economic growth in rural communities.